Electron optics and electron-beam devices - Zhigarev, A. (Mir, 1975)
This book, primarily intended for university students studying the "Electron optics and electron-beam devices" course, presents the fundamentals of electron optics including intensive-beam optics and detailed description of basic compoments of electron-beam devices as well as the most common types of such devices.